(untitled) (Research, Society and Development, 2020)
The aim of the study was to outline the social, economic and environmental profile of communities in the municipality of Acará, Pará, Brazil. The research took place in the communities of Monte Carmelo do Igarapé Retiro, Nazaré do Alto Igarapé Ipitinga, Nazaré do Baixo Igarapé Ipitinga, Roma and Vera Cruz, from August to November 2019. A semi-structured questionnaire was used for 65 families. We observed that 71% of the interviewees are male and farmers. The predominant age range was 31 to 50 years old and 78% of the interviewees have completed elementary school. Family farming is practiced without the use of fertilizer and pesticides, as producers are aware of the environmental impact they can cause. Among the most cultivated and commercialized vegetables is açaí (Euterpe oleracea Mart.). The monthly income of families comes from the sale of products from agriculture, in addition to the practice of handicrafts and extraction forest, and receives social benefits, such as the family allowance and retirement. All respondents say they had an environmental problem in the communities. They highlighted climate change in the region and the contamination of streams by industrial effluents. The production of palm oil was pointed out by the interviewees, the main cause of this contamination and they claim that all residents had to build artesian wells in their homes, to supply their needs. In conclusion, the socioeconomic profile showed an overview of the communities and the introduction of a palm oil producing company in the region has contributed to negative socio-environmental changes, mainly with the contamination of the streams. As future studies, we suggest training in solid waste and effluent treatment techniques in these communities, with the objective of mitigating the environmental impacts observed in the present study.